PERAN PROMOSI DIGITAL DALAM PENGEMBANGAN PARIWISATA BUDAYA DI CIREBON - Yohandi, Iklimah; Putra, Gilang Pratama; supriyadi, tedi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the limited effectiveness of digital promotion in developing cultural tourism in Cirebon. It aims to analyze the role of digital promotion and propose an integrated framework. A qualitative case study was conducted using observation, interviews, and documentation, analyzed through thematic analysis with NVivo 12. The results show that digital promotion enhances destination visibility and tourist attraction, but its effectiveness is constrained by limited human resources, weak content management, and insufficient stakeholder collaboration. The study implies that integrated digital strategies, strategic content development, and collaborative governance are essential to support sustainable cultural tourism development. Keywords: Digital Promotion; Cultural Tourism; Social Media; Tourism Development; Cirebon